AGAMA DAN POLITIK DI KALIMANTAN SELATAN - AM, Mirhan (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
Politics cannot be separated from religion. The combination between them have uttered the political religious thoughts in order to create a harmonious and peaceful life in the nation. Religious beliefs can impact laws in common, such as the thought of sodomy and incest is a sin, so it become illegal in national laws. While religion gives legitimacy to the government to act. Religion is deeply embedded in the lives of people in industrial societies and non-industrial, so its presence may not be felt in the political sphere. But it is considered or not, religion has a role to form a political power. In Islam, Medina Charter contained aspects of life either it comes to diversity as well as a matter of policy set to pluralistic society, cannot be regarded as a statement of the establishment of the Islamic State. Yet, in this contemporary era, the teachings of Islam were able implied in issues of national state and life of the community.